Behaviours involved in the role of victim and aggressor in bullying: Relationship with physical fitness in adolescents - Juan de Dios Benítez-Sillero (Public Library of Science (PLoS), 2021)
Physical fitness is related to well-being and health. Adolescence is a key period in the psychological and social development of the person, in which interpersonal relationships gain strength, being bullying a type of violence that can affect the personality of those involved. At present, there is not enough research to determine the relationships between bullying and physical condition. The purpose of this study is to find out if there are any relationships among physical fitness, victimisation, and aggression in bullying, and to identify these behaviours. This is a descriptive study done in 1035 adolescents aged 12 to 17 years (M = 14.67, SD = 1.49). The European Bullying Intervention Project Questionnaire (EBIPQ) scale was used, and anthropometric characteristics of weight and height were measured. In addition, physical fitness tests from the Eurofit battery, sit-and-reach, 30-second sit-ups, horizontal jump, manual dynamometry, and 20-meter Multistage Shuttle Run Test (SRT) were included. The relationships between variables were analysed using Spearman correlations, linear regressions, and ordinal regressions. The most relevant findings indicate an inverse relationship between being a victim of bullying and having a better cardiorespiratory cardiovascular endurance. These also show a direct relationship between being a bully and skeletal muscle strength measured through the horizontal jump, 30-second sit-ups, and manual dynamometry tests. Theoretically, we can conclude that physical condition can be considered a predictor to consider in bullying. Specifically, cardiorespiratory fitness, in addition to its multiple physical and mental benefits, may be a protective element against bullying victimisation. In contrast, muscular strength, especially in boys, may be an important predictor, especially in the physical component, of aggression in bullying.